Orientation for Development of Accounting Services Market in Vietnam Today - Hanh, Luong Thi Hong (Archives of Business Research, 2025)
Currently, the trend of opening up and integrating together with the needs of domestic enterprises makes the accounting service market in Vietnam considered very potential. This is a development opportunity for accounting service businesses and accounting practitioners, but it is also a challenge for the newly formed and recognized Vietnamese accounting service market, which is still very young and full of potential. This article analyzes some of the contents that need to be noted in the work of inspecting accounting service activities, thereby providing orientations for the development of the accounting service market in Vietnam until 2030.